Textbook of work physiology : physiological bases of exercise - Astrand, Per-Olof.; Rodahl, Kaare (New York : McGraw- Hill Book Company, 1986)
Textbook of Work Physiology. 15 Chapters (739 pgs) looking at a variety of physiological concepts. For example, muscles and their contraction, respiration, physical performance, physical training, temperature regulation, factors affecting performance
Includes references and index.
Keywords: Work -- Physiological aspects; Exercise -- Physiological aspects; Physical Education and Training